Current Problems of Administering Public Property in Airports - N. A. Rezina; E. V. Kuzmina (Сибирское юридическое обозрение, 2015)
The article considers the issues of improving the legal regulation of the airports’ state property management. The authors estimate the causes of problems arising in airport management as well as government schemes aiming to develop this branch.